Imaging Analysis of Onodi Cells on Cone-Beam Computed Tomography - Ali, Ibrahim K.; Sansare, Kaustubh; Karjodkar, Freny; Saalim, Mohd (International Archives of Otorhinolaryngology, 2020)
Introduction Onodi cells are the most posterior ethmoid air cells, and extend superolaterally to the sphenoid sinus. The identification of Onodi cells is essential to because they can have some significant anatomic variations and relationships to vital adjacent structures, like the optic canal, the sphenoid sinus, and the internal carotid artery.Objective The present study aimed to assess the prevalence of Onodi cells and their position with respect to sphenoid sinus. To the authors' best knowledge, this is the first study that uses cone-beam computed tomography (CBCT) to assess the prevalence and position of Onodi cells.Methods We collected CBCT scan records from November 1st, 2016, to July 31st, 2017; the patients who fulfilled the eligibility criteria were included in the present study. The CBCT scans were reviewed by two independent observers. The descriptive statistics was performed using the Statistical Package for the Social Sciences (SPSS, SPSS, Inc., Chicago IL, US) software, version 17.0. A cross-tabulation of gender with the presence and position of Onodi cells was evaluated using the Chi-squared (χ2) test. The inter- and intraobserver agreements were evaluated using Kappa (κ) statistics.Results Onodi cells were identified in 86 (42.8%) out of 201 patients. A subgroup analysis revealed that Onodi cells were present in 45 (43.3%) female and 41 (42.3%) male patients. The position of the Onodi cells was superior with respect to the sphenoid sinus in 43 (50%) of the patients, superolateral in 36 (41.9%), and lateral to the sphenoid sinus in 7 (8.1%) of the patients.Conclusion The present study indicated a high prevalence of Onodi cells, with approximately equal distribution among males and females, and mostly superior in position in relation to the sphenoid sinus.
Keywords: onodi cell; optic neuritis; cone-beam computed tomography; endonasal transsphenoidal technique